An approach to hybridisation of embedded system networks - Rajasekhar, J; JKR Sastry, Dr (International Journal of Engineering and Technology, 2018)
Embedded systems can be networked using either wired or wireless technologies. ES systems when networked using wires can communicate serially over a bus using the technologies such as CAN, I2C, USB, RS485, and Fire wire. These standards differ in many ways which include arbitration, synchronization, address resolution, timing, type of communication etc. Embedded systems can also be network using wireless technologies which exits in many versions.Several applications these days are requiring more than one communication technology. Several sub-systems are developed using a networking method and it requires that the subsystems that are networked using different technologies are to be networked further for realizing entire application. Such a network needs to deal with many of the heterogeneous communication system leading to an issue of hybridisation. In this paper various issues/approaches that need to be addressed for hybridising of the ES networks have been presented.Â Â